Proceedings of the inaugural International Summit for Medical Nutrition Education and Research. (November 2016) - Laur, C.; Ball, L.; Ahankari, A.S.; Avdagovska, M.; Crowley, J.; Deen, D.; Douglas, P.; Hark, L.; Kohlmeier, M.; Luzi, L.; McCotter, L.; Martyn, K.; et al.
Abstract: Medical Nutrition Education (MNE) has been identified as an area with potential public health impact. Despite countries having distinctive education systems, barriers and facilitators to effective MNE are consistent across borders, demanding a common platform to initiate global programmes. A shared approach to supporting greater MNE is ideal to support countries to work together. In an effort to initiate this process, the Need for Nutrition Education/Innovation Programme group, in association with their strategic partners, hosted the inaugural International Summit on Medical Nutrition Education and Research on August 8, 2015 in Cambridge, UK. Speakers from the UK, the USA, Canada, Australia, New Zealand, Italy, and India provided insights into their respective countries including their education systems, inherent challenges, and potential solutions across two main themes: (1) Medical Nutrition Education, focused on best practice examples in competencies and assessment; and (2) Medical Nutrition Research, discussing how to translate nutrition research into education opportunities. The Summit identified shared needs across regions, showcased examples of transferrable strategies and identified opportunities for collaboration in nutrition education for healthcare (including medical) professionals. These proceedings highlight the key messages presented at the Summit and showcase opportunities for working together towards a common goal of improvement in MNE to improve public health at large. Highlights: Key points of 2015 International Summit on Medical Nutrition Education & Research. Identified shared needs across regions. Showcased opportunities to work together to improve medical nutrition education.